Attenuation of lung cancer stem cell tumorigenesis and metastasis by cisplatin. (1st October 2014) - Wang, Shenxu; Ma, Sai; Li, Xiujuan; Xue, Zengfu; Zhang, Xiaotian; Fan, Weiwei; Nie, Yongzhan; Wu, Kaichun; Chen, Xiaoyuan; Cao, Feng
ABSTRACT Purpose: To investigate the effect of cisplatin on the growth and metastasis abilities of lung cancer stem cells (CSCs) via molecular imaging. Materials and Methods: The expression changes of lung CSCs cell marker in A549-Luc-C8 human non-small-cell lung cancer (NSCLC) cell line with or without cisplatin treatment were detected by flow cytometry. The tumorigenesis and metastasis abilities of A549-Luc-C8 cells were monitored both in vitro and in vivo, and the mechanism was assessed by gene sequencing. Results: About 1%–2% of CSCs were detected in A549-Luc-C8 cells and decreased CSCs percentage was observed after cisplatin treatment. Attenuated tumorigenesis and metastasis abilities of A549-Luc-C8 cells were found in cisplatin treated group. Conclusions: Decreased percentage of CSCs in A549-Luc-C8 cells can be induced by cisplatin treatment, which may partly be attributed to the attenuated expression of growth factors.